Long-term changes of regional ozone in China: implications for human health and ecosystem impacts - Xiaobin Xu; Weili Lin; Wanyun Xu; Junli Jin; Ying Wang; Gen Zhang; Xiaochun Zhang; Zhiqiang Ma; Yuanzhen Dong; Qianli Ma; Dajiang Yu; Zou Li; et al. (Elementa: Science of the Anthropocene, 2020)
The first Tropospheric Ozone Assessment Report (TOAR) provides information on present-day distributions and long-term trends of ozone metrics relevant for climate change, human health, and vegetation. However, only few results are available in TOAR for China due to limited long-term ozone observations. Here, we present an integrated analysis of long-term measurements of surface ozone from eight sites distributed in the North China Plain (NCP) and Yangtze River Delta (YRD), the relatively underdeveloped region Northeast China, and the remote regions in Northwest and Southwest China. Trends and present-day values for seven annual and five seasonal ozone metrics were calculated following the TOAR methodologies. We compare the seasonal and diurnal cycles of ozone concentrations as well as the present-day values of ozone among sites and discuss the long-term trends in the ozone metrics. Large and significant increases of ozone are detected at the background site in the NCP, moderate increases at the global baseline site in western China, significant decreases at the northwestern edge of China, and nearly no trend at other sites. Extremely high values of ozone occurred in the NCP and YRD, particularly in warmer seasons. The present-day levels of summer ozone metrics in the NCP are much higher than the thresholds set in TOAR for the highest value groups of ozone metrics. The summer ozone metrics at the Shangdianzi background site in the NCP indicate increases at rates of more than 2%/yr during 2004–2016. In contrast, ozone at the Lin’an background site in the YRD was constant over the period 2006–2016. Our results fill some knowledge gaps in spatiotemporal changes of ozone in China and may be of useful in the assessment of ozone impacts on human health and vegetation.